2016
DOI: 10.1093/abbs/gmv133
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol inhibits the growth and metastasis of cholangiocarcinoma <italic>in vitro</italic> and <italic>in vivo</italic>

Abstract: Kaempferol is a flavonoid that has been reported to exhibit antitumor activity in various malignant tumors. However, the role of kaempferol on cholangiocarcinoma (CCA) is largely unknown. In this article, we found that kaempferol inhibited proliferation, reduced colony formation ability, and induced apoptosis in HCCC9810 and QBC939 cells in vitro. Results from transwell assay and woundhealing assay demonstrated that kaempferol significantly suppressed the migration and invasion abilities of HCCC9810 and QBC939… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…The consumption of kaempferol has been reported to significantly increase the cytotoxic effects of cisplatin 29. In in vivo xenografted mouse models, kaempferol inhibits the growth and metastasis of cholangio-carcinoma in vivo 30. The volume of subcutaneous xenograft in the kaempferol-treated group was smaller than that in the cholangiocarcinoma control group 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of kaempferol has been reported to significantly increase the cytotoxic effects of cisplatin 29. In in vivo xenografted mouse models, kaempferol inhibits the growth and metastasis of cholangio-carcinoma in vivo 30. The volume of subcutaneous xenograft in the kaempferol-treated group was smaller than that in the cholangiocarcinoma control group 30.…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo xenografted mouse models, kaempferol inhibits the growth and metastasis of cholangio-carcinoma in vivo 30. The volume of subcutaneous xenograft in the kaempferol-treated group was smaller than that in the cholangiocarcinoma control group 30. Kaempferol also suppressed the number and volume of metastasis foci in the lung metastasis model 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HCCC9810 and QBC939 cells, kaempferol suppressed proliferation, reduced colony formation, and induced apoptosis. Additionally, it (a) decreased Bcl‐2 expression, (b) increased Fas, Bax expressions, (c) enhanced cleaved‐caspase 3, cleaved‐caspase 8, cleaved‐caspase 9, and cleaved‐PARP, (d) down‐regulated levels of phosphorylated TIMP2, AKT, and MMP2, and (e) inhibited the number and volume of metastasis foci in lung metastasis model (Qin, Cui, Yang, & Tong, ).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Another study examined the inhibitory effect of kaempferol on cholagiocarcinoma. The in vitro and in vivo studies demonstrated that kaempferol decreases the level of Bcl‐2 and also enhances the level of Bax, Fas, cleaved Caspases 3, 8, and 9 as well as cleaved‐PARP, leading to the inhibition of growth and metastasis of cholangiocarcinoma (Qin et al, ).…”
Section: Introductionmentioning
confidence: 99%